The Royal Brussels Horn Sound: Flemish Romantic Music on Period Instruments - Mengal, Martin-Joseph 1784-1851; Dubois, Léon 1859-1935; Bergé, Luc; Billiet, Jeroen (Brussels Fuga Libera, 2009)
First part of a new Fuga Libera cycle, elaborated with the masters of the Conservatoire Royal Flamand de Bruxelles (Royal Flemish Conservatory of Brussels), this CD, highlights to Luc Bergé’s art, presenting two important masterpieces for chamber music. They are performed in octet and in sextet of ancient French horns by the soloist of the l’ Orchestre des Champs Elysées and seven of his disciples.The Octuor pour Huit Cors Chromatiques (Octet for eight Chromatic French horns) of Léon Dubois (1859-1935) revives the figure of a director of the Brussels Conservatory who was also a very fine – and pretty Wagnerian – composer “end of century”. It is performed on eight historical horns from Van Cauwelaert’s workshop, the main competitor in Brussels of the famous Mahillon, Wagner’s official supplier. Those horns of two types – from Liege and from Ghent (!) – are aesthetically in-between French and German horn, so different in those times. While the Grand Octuor pour six Cors et deux Trombones (Great octet for six horns and two trombones) of Martin-Joseph Mengal (1784-1851) was written between 1817 and 1820 by the future first director of the Royal Conservatory of Ghent. At the time, Mengal was still in Paris, in Antonin Reicha’s class, greatly admired by the famous Dauprat. The Octet is performed on six historical French style horns.
Keywords: Conservatoire royal de musique (Brussels, Belgium); 19th Century (1801-1900); Instrumental music; Horn; Historically informed performance; Brussels (Belgium)